A Dean, A Scholar, A Friend : Texts in appreciation of Markus Granlund - (:unkn) unknown (fi=Turun yliopisto, Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2017)
Markus Granlund is an almost staggeringly many-sided person. He is a prolific scholar of first class, the Dean of the Turku School of Economics, capturing and skilful teacher, a family man with four sons, a super-talented ice-hockey player and what not. Everything he does seems to happen with ease and calmness. This is not because his work-life would be without challenges. These are not easy times to be a Dean at a Finnish university, but demanding and turbulent indeed. It seems to be a “new normal” that funding is a continuously bothering issue and so is indicating systematic high volume and quality performance, nowadays measured in numerous dimensions and in accelerating pace. As the Dean of TSE, Markus has not saved himself from super-committed work and putting himself fully at stake – and turned out to be a successful dean. It is certainly of much help that Markus is a man who can find humour even in the toughest situations and conditions. This is a fabulous feature in anybody: sense of humour, especially warm irony, is an ice-breaker and relaxer for all. It is also almost impossible to pull his leg. He seems always ready to see directly behind such attempts and to me this is one aspect of his superb sense of humour. Working with him has never been only work, but always a lot of fun, too. Markus is my closest colleague of all times. We started collaborating in the early 1990s, when we conducted a survey research on cost and management accounting practices in Finland. Soon thereafter we were jointly responsible for the scholarly program of the EAA Congress that was held in Turku in 1993 as members of the organizing committee. Oh boy that we had good times in doing that! Over the years, Markus and I have conducted several management accounting studies together, most of which leading to an international journal publication. Our collaboration has always taken place in the spirit of total quality in our work: to carry out each and every bit of the work processes so that quality is ensured right from the beginning. This “total quality principle” was essential in the biggest joint project I have conducted with Markus. It was teaming up for running the editorial office of the European Accounting Review in 2000-2005 – Markus first as an Assistant Editor and soon an Associate Editor, splendidly supporting me as the Editor. There are no words to indicate how thankful I am for the highly professional scholarly and administrative support that Markus offered me during those hectic years, during which we so intensively worked for developing the journal towards being a more and more respected outlet for serious scholarly publications in accounting. We shared the same vision of making the journal globally known as the paradigmatically, methodologically and theoretically open-minded accounting journal. Our joint efforts also paid off: European Accounting Review has been an ISI indexed journal now for more than ten years and it is ranked at level 3 in the ABS ranking (and Jufo 2 in Finland). That said, journal and university rankings and league tables have never been the major driving force for Markus. Yet he knows we are in the world with others, so we cannot entirely omit rankings and that sort of things. But Markus is consistent in not allowing the “tail wag the dog” even in these times of publish or perish. He has systematically resisted the lures of letting the measures and proxies of academic performance take the primary role in academic work. Good scholarship is a central value for Markus, always over and above just looking great in terms of performance indicators. It adds to the picture of many-sidedness of Markus that, in addition to being an Accounting Professor, he has also held a position as a Professor of Information Systems Science at TSE for some time. In fact, Markus is certainly one of the leading management accounting and information systems scholars in the world. Despite his being the Dean, he is an Associate Editor of International Journal of Accounting Information Systems. Along this line of thought, Markus has always been an extremely international scholar. He has, for instance, visited Copenhagen Business School and University of Technology Sydney for longer periods. He has collaborated with many scholars both nationally and internationally. The works in this volume, which are prepared in the huge appreciation of Markus Granlund celebrating his 50th birthday, nicely echo the many-sidedness of the person they are written for. They form a collection of several kinds of texts: scholarly pieces, personal recollections and poems. All these works are clearly conducted with warm thoughts on Markus, a chap of great wit and charm. I wish to express my sincere thanks to all contributors to this volume, feeling assured that Markus will pretty curiously take a look at these works that are written for him with caring collegial and friendly appreciation. Special thanks are devoted to Karolina Laine, who has greatly helped me in the editorial work for this book.